Enhanced humidity-sensing performance of (Zr4+/Sb5+)-codoped TiO2 ceramics with giant dielectric properties - Noppakorn Thanamoon; Nateeporn Thongyong; Kaniknun Sreejivungsa; Narong Chanlek; Prasit Thongbai (Journal of Advanced Ceramics, 2025)
In this study, (Zr0.5/Sb0.5)xTi1−xO2 ceramics with x = 0.01, 0.025, and 0.05 were prepared via the solid-state reaction (SSR) method. A pure phase of rutile TiO2 with a highly dense microstructure and relative density (ρr) higher than 96% was detected in all the sintered ceramics. The mean grain size was reduced, but the dielectric permittivity (ε′) increased. The giant dielectric properties were tested to investigate their possible use in capacitors and capacitive humidity sensors under various relative humidity (RH) levels ranging from 30% to 95% RH. (Zr0.5/Sb0.5)xTi1−xO2 ceramics present a giant ε′ of ~(4.82‒7.39)×104 and a low loss tangent (tanδ ≈ 0.031‒0.106 at 1 kHz), indicating attractive giant dielectric properties. This observation was attributed to both intrinsic and extrinsic effects. For the humidity sensing properties, the best humidity sensing properties were observed in the ceramics with x = 0.05, with a sensitivity of ~237%pF/%RH, a low hysteresis error (~1.6%), and fast response/recovery time of ~12 s/16 s at 1 kHz. The point defects of SbTi⋅ and VO⋅⋅ were claimed to be active centers for water absorption. Furthermore, impedance spectroscopy (IS) analysis revealed that changes in the dielectric properties with varying RH levels were also influenced by interfacial polarization at the surface layer and grain boundaries.